Development of a diagnostic tool for condition monitoring of rotating machinery - Lin, T.; Tan, A.; Howard, Ian; Pan, J.; Crosby, P.; Mathew, J. (Asset Management Council, 2011)
This paper presents an overview of the CRC for Infrastructure and Engineering Asset Management (CIEAM)'s rotating machine health monitoring project and the status of the research progress. The project focuses on the development of a comprehensive diagnostic tool for condition monitoring and systematic analysis of rotating machinery. Particularly attention focuses on the machine health monitoring of diesel engines, compressors and pumps by using acoustic emission and vibration-based monitoring techniques. The paper also provides a brief summary of the work done by the three main research collaborating partners in the project, namely, Queensland University of Technology (QUT), Curtin University of Technology (CUT) and the University of Western Australia (UWA). Preliminary test and analysis results from this work are also reported in the paper.